Estimating synchronous demographic changes across populations using hABC and its application for a herpetological community from northeastern Brazil. Issue 18 (24th August 2017) - Gehara, Marcelo; Garda, Adrian A.; Werneck, Fernanda P.; Oliveira, Eliana F.; da Fonseca, Emanuel M.; Camurugi, Felipe; Magalhães, Felipe de M.; Lanna, Flávia M.; Sites, Jack W.; Marques, Ricardo; Silveira‐Filho, Ricardo; São Pedro, Vinícius A.; et al.
Abstract: Many studies propose that Quaternary climatic cycles contracted and/or expanded the ranges of species and biomes. Strong expansion–contraction dynamics of biomes presume concerted demographic changes of associated fauna. The analysis of temporal concordance of demographic changes can be used to test the influence of Quaternary climate on diversification processes. Hierarchical approximate Bayesian computation (hABC) is a powerful and flexible approach that models genetic data from multiple species, and can be used to estimate the temporal concordance of demographic processes. Using available single‐locus data, we can now perform large‐scale analyses, both in terms of number of species and geographic scope. Here, we first compared the power of four alternative hABC models for a collection of single‐locus data. We found that the model incorporating an a priori hypothesis about the timing of simultaneous demographic change had the best performance. Second, we applied the hABC models to a data set of seven squamate and four amphibian species occurring in the Seasonally Dry Tropical Forests (Caatinga) in northeastern Brazil, which, according to paleoclimatic evidence, experienced an increase in aridity during the Pleistocene. If this increase was important for the diversification of associated xeric‐adapted species, simultaneous population expansions should be evident at the community level. We found a strong signal of synchronous population expansion in the Late Pleistocene, supporting the increase of the Caatinga during this time. This expansion likely enhanced the formation of communities adapted to high aridity and seasonality and caused regional extirpation of taxa adapted to wet forest.